Application of the Web 2.0 Technologies Podcast and Vidcast for Formation and Development of Listening Comprehension Skill in an Extended Englishtraining Course in Eighth Grade - Rumen Hristov (Педагогически форум)
Low levels of listening comprehension skills in English is observed in many students. As a specific method, which can both cover mobile technologies and combine them with training, is the application of technology for podcasting and vidcasting/vodkasting. Podcasts and podcasts can provide authen-tic, up-to-date and easily accessible material, making them extremely useful when learning foreign languages. Their application makes learning freer and independent by introducing more interesting elements; gives greater freedom and independence to participants in the lesson. Students can listen to the material on the bus or while going to the gym.